Taxes do affect corporate financing decisions: The case of Belgian ACE - Savina Princen (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper, I use difference-in-differences regressions to measure how the debt tax shield affects the capital structure of a company. By comparing the financial leverage of treatment and control companies before and after the introduction of an equity tax shield, I infer the impact of the tax discrimination between debt and equity. Consistent with the theoretical prediction, the estimated results show that the introduction of an equity tax shield has a significant negative effect on the financial leverage of a company. This effect amounts to approximately 2-7%, meaning that a classical tax system encourages companies to use on average 2-7% more debt than when there is an equal tax treatment of debt and equity.
Keywords: G30; H25; K34; 330; allowance for corporate equity; corporate financing decisions; Kapitalstruktur; Entscheidung; Unternehmensbesteuerung; Eigenkapital; Steuerliches Anrechnungsverfahren; Steuerwirkung; Belgien